Examining the Collection "Akhar e Shahnameh" by Mehdi Akhavan Sales from the Perspective of Critical Discourse Analysis - Bahador Bagheri; Mohamad Rezaie; Ali Mollamohammadi (مطالعات زبانی و بلاغی)
"Critical Discourse Analysis" is a scientific and interdisciplinary approach that is rooted in critical linguistics and its main purpose is to study the use of language in society and politics. Critical discourse analysis deals with literature as communication texts through stylistics, literary criticism, and text analysis studies. Three issues of "language, ideology and power" are fundamental concepts in this approach. Discourse scholars try to discover the meaning - and more importantly - the ideology hidden in the text by describing and analyzing the linguistic structures of the texts and activating the text in its non-linguistic context. Three Nimai poems from the collection "Akhar e Shahnameh "composed by Mehdi Akhavan Sales have been studied in this article. The main question of this research is how Akhavan Sales uses various linguistic possibilities in articulating the discourse it believes in. The method of analysis of these poems is based on the three-dimensional model of "Norman Fairclough", a social linguist who has exceeded the analysis of critical discourse by adding levels of interpretation and explanation, beyond the level of description. Based on this model, it is clear that Akhavan Sales has articulated its various discourse and ideological layers by consciously using the possibilities of linguistic structures, including sounds, words and syntactic structure of the text. De-legitimizing the discourse of the dominant powers, highlighting the shortcomings of the existing discourse and despairing of changing the chaotic situation to a desirable and organized situation are the discourse-building elements of Akhavan Sales poetry in this collection.